We hate that school: a content analysis of rivalries and student-run Barstool Sports accounts - Friesen, Jonathan Cody (Kansas State University, 2021)
Rivalries are a unique aspect of college life. The longstanding traditions that these rivalries bring to individuals provide a sense of excitement on campus. Still, sometimes these rivalries can cross a line between competition on the field and a feud in the stands. As technology has developed and the role of social media is constantly changing, the trash-talk between fans of rival schools is becoming more public and, in some cases, more uncivil. The study examines multiple college sports rivalries and interactions on Twitter among student-run Barstool Sports accounts. Specifically, this study looks into the behavior towards rivals using eight Barstool Sports student-run accounts across four different college rivalries. This study found six different characteristics, which can inform future studies of individual fan behavior on social media, three of which are negative, namely (1) Glory out of reflected failure. (2) Replying to the rival account. (3) Targeting the rival using stereotypes. The study found three positive instances that these accounts relied upon: (4) Using humor relatable to students at the school. (5) Creating conversations online for fans of the school. (6) Expressing pride for alumni or university. The Social Identity Theory is used to identify the in-group behaviors of sports fans and the created out-group biases. Uses and Gratifications Theory was also used to explain the data. This study aims to fill a gap in the existing literature on negative behavior on social media in college athletics and explicate further the concept of glory out of reflected failure or schadenfreude between rivals. As the guidelines for social media change, this study could help provide insight on the behavior of sports fans who use these accounts like Barstool as a catalyst to fuel the hatred towards a rival.
Keywords: Barstool Sports; Glory out of reflected failure; Social media; Uses and gratifications theory; Social identity theory